Naptics: Convenient and Continuous Blood Pressure Monitoring during Sleep - intern), Andrew Carek (research; Holz, Christian (Interactive, Mobile, Wearable and Ubiquitous Technologies, 2018)
Normal circadian rhythm mediates blood pressure during sleep, decreasing in value in healthy subjects. Current methods to monitor nocturnal blood pressure use an active blood pressure cuff that repeatedly auto-inflates while the subject sleeps. Since these inflations happen in intervals of thirty minutes to one hour, they cause considerable sleep disturbances that lead to false measurements and impact the person's quality of sleep. These blood pressure samples are also just spot checks and rarely exceed 10–15 values per night. We present Naptics, a wearable device woven into shorts. Naptics passively monitors the wearer’s blood pressure throughout the night—continuously and unobtrusively—without disturbing the user during sleep. Naptics detects the micro-vibrations of the wearer's body that stem from the heartbeat and senses the optical reflections from the pulse wave as it propagates down the wearer's leg. From the timing between these two events, Naptics computes the pulse transit time, which correlates strongly with the user's blood pressure. Naptics' key novelty is its unobtrusive approach in tracking blood pressure during the night. Our controlled evaluation of six subjects showed a high correlation (r = 0.89) between Naptics' calibrated mean arterial pressure and cuff-based blood pressure. Our in-the-wild evaluation validates Naptics in tracking five participants' blood pressure patterns throughout four nights and compares them to before and after cuff measurements. In a majority of the nights, Naptics correctly followed the trend of the cuff measurements while providing insights into the behavior and the patterns of participants' nocturnal blood pressure. Participants reported high sleep quality in sleep diaries after each night, validating Naptics as a convenient monitoring apparatus. More information on the Naptics project page.